Future Climatic Projections and Hydrological Responses in the Upper Beijiang River Basin of South China Using Bias‐Corrected RegCM 4.6 Data. Issue 19 (27th September 2021) - Chen, Xiaoli; Chen, Wenjie; Huang, Guoru
Abstract: The adverse effects of climate change on future extreme rainfall‐runoff events are posing severe challenges to flood control departments. Aimed at projecting future extreme rainfall‐runoff events over the Upper Beijiang River Basin of South China, regional climate model (RegCM 4.6) was used for dynamic downscaling three global climate models (GCMs) with two representative concentration pathways (RCP4.5 and RCP8.5) in two future periods (F1: 2016–2035 and F2: 2066–2085). Precipitation bias correction was carried out using an improved quantile mapping method. The future extreme precipitation events were analyzed using four extreme precipitation indices. The Soil and Water Assessment Tool model was established to simulate historical runoff and project future runoff. Three extreme runoff indices were defined to analyze future extreme runoff. The results showed that the bias correction effect was obvious, and the ability of the RegCM outputs driven by GCMs to capture the precipitation characteristics was obviously enhanced. Future extreme precipitation events will be more intense with almost all the four extreme precipitation indices showing increasing trends in future periods. Moreover, the future monthly runoff have basically increased and almost all the extreme runoff indices have increased in future periods with the average annual runoff, the total runoff in very wet days and the number of very heavy runoff days increasing by about 7%, 25%, and 35% respectively. Overall, responses and mitigation strategies should be developed regarding future extreme rainfall‐runoff events. Key Points: Using the improved quantile mapping method to correct the regional climate model rainfall can better capture the rainfall characteristics Future extreme precipitation events will be more intense with the extreme precipitation indices showing increasing trends There will be more extreme runoff events in the future with the mean annual runoff, R95r and the R3000 increasing by about 7%, 25%, and 35% respectively